2018
DOI: 10.1186/s40733-017-0038-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge and education relating to asthma during pregnancy among women of childbearing age

Abstract: BackgroundMisconceptions about medications’ safety can lead pregnant women with asthma to stop their medications, resulting in asthma-related neonatal morbidity and mortality. Our aim was to assess the level of pregnancy-related asthma knowledge and education about asthma medications’ safety, among women of childbearing age with a history of bronchial asthma.MethodsA cross-sectional survey of convenience sample of outpatient clinic attendees of Pulmonary, Family Medicine and Obstetrics & Gynecology among women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Self‐reported changes to asthma treatment were documented in five studies of pregnant women with asthma, using (online) questionnaires or interviews . In a survey of 102 pregnant women with asthma in Australian, 37% reported controller use prior to pregnancy, yet only 18% reported use during pregnancy .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Self‐reported changes to asthma treatment were documented in five studies of pregnant women with asthma, using (online) questionnaires or interviews . In a survey of 102 pregnant women with asthma in Australian, 37% reported controller use prior to pregnancy, yet only 18% reported use during pregnancy .…”
Section: Resultsmentioning
confidence: 99%
“…An additional study reported 33% had ceased or reduced asthma medication, based on face‐to‐face interviews (N = 58) . In a questionnaire‐based study of 171 women with asthma, 47% reported to have ceased, or wanted to cease, their asthma medication during pregnancy. Moreover, a study of 123 pregnant women with asthma presenting to an emergency department reported that 16% had ceased ICS medication prior to the event …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor asthma control during pregnancy is associated with adverse maternal outcomes (e.g., hypertension, gestational diabetes, preterm delivery, maternal mortality) and neonatal outcomes (e.g., congenital malformation, hospitalization, and death) (Murphy and Schatz, 2014;Baghlaf et al, 2017;McLaughlin et al, 2018). The U.S. Department of Health and Human Services recommendations prioritize asthma control over possible pharmaceutic side effects related to pregnancy (National Heart Lung et al, 2005), as it has been shown that effective perinatal control of asthma has been associated with improved outcomes for both mother and infant (Ibrahim et al, 2018;Murphy and Schatz, 2014;Al Ghobain et al, 2018;McLaughlin et al, 2018).…”
Section: Asthma In Pregnancy and Hm Usementioning
confidence: 99%